Process parameter sensing for remote hyperbaric welding - Papadopoulos, Konstantinos (Cranfield University, 2009)
Pipeline ovality and equipment set-up variations pose a challenge for offshore remote hyperbaric welding operations using a fillet welded sleeve for pipeline repair. The distance from the torch to the pipe should be kept as constant as possible to maintain optimum welding process stability. The work of this research project was focused on using through-the-wire sensing and the establishment of the feasibility of Dip Resistance measurement as a suitable method for real time contact tip to work-piece distance estimation and control under Hyperbaric Welding conditions. Analysis of cases of Dip Resistance application in 1 Atm and factors of influence has been performed and their relevance and importance for the RPRS program is examined. Suitability of the Dip Resistance is concluded and verification of this under hyperbaric conditions is tested. For this purpose, a data acquisition hardware system was built and software was written using Lab VIEW 7.1 in order to acquire and analyse the welding signals in real-time and store the signals for later analysis. A second program focused on the analysis of the Dip Resistance information was written using Lab VIEW 7.1 in order to analyse the experimental data off-line and to evaluate the results in more detail. Experiments were made using various welding patterns so as to determine the feasibility of the method of the use of Dip Resistance information as a method for real-time estimation and control of the weld process. Based on these results, three detection algorithms were evaluated and the most suitable one was selected for further investigation. Initial investigation on other factors of influence like the length of the welding current’s path and resistance variation with temperature is examined. The results from the experiments and their off-line analysis are presented and a discussion of the results is presented. It is concluded that real-time control of the contact tip to work-piece distance torch may be achieved in real-time using dip resistance monitoring if it used in conjunction with the welding current and welding voltage signals allows achievement of robust control. Suggestions for further study and achievement of a complete solution are presented.